2014
DOI: 10.1111/jph.12339
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Distribution and Effects on Cassava Cultivars of Cassava Brown Streak Viruses in Malawi

Abstract: Cassava brown streak disease (CBSD) has emerged as a major threat to cassava (Manihot esculenta) in eastern and southern Africa. CBSD was first reported in Malawi in the 1950s, but little data on the distribution and epidemiology of the disease are available. A diagnostic survey was therefore conducted in Malawi to determine the distribution, incidence and diversity of viruses causing the disease, and to characterize its effects on local cassava cultivars. Diagnostic tests confirmed the presence of cassava bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…For example, in Uganda, where the latest CMD pandemic first emerged in the 1990s, the IITA varieties were resistant to CMD, and to a lesser extent, cassava brown streak disease (CBSD), caused by cassava brown streak viruses (CBSVs) in East Africa (Ntawuruhunga et al, 2013; Pariyo et al, 2015; Patil et al, 2015). Similar successes have been recorded in other eastern and southern African countries (Ntawuruhunga et al, 2013; Mbewe et al, 2015; Masinde et al, 2016). In Zambia, eight IITA varieties outperformed local varieties significantly, resulting in increased yields, household income, and food security (Khonje et al, 2015).…”
Section: Cmg Resistance Breedingsupporting
confidence: 85%
“…For example, in Uganda, where the latest CMD pandemic first emerged in the 1990s, the IITA varieties were resistant to CMD, and to a lesser extent, cassava brown streak disease (CBSD), caused by cassava brown streak viruses (CBSVs) in East Africa (Ntawuruhunga et al, 2013; Pariyo et al, 2015; Patil et al, 2015). Similar successes have been recorded in other eastern and southern African countries (Ntawuruhunga et al, 2013; Mbewe et al, 2015; Masinde et al, 2016). In Zambia, eight IITA varieties outperformed local varieties significantly, resulting in increased yields, household income, and food security (Khonje et al, 2015).…”
Section: Cmg Resistance Breedingsupporting
confidence: 85%
“…Historically, CBSD was thought to be caused by two distinct viruses, cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV), but Ndunguru et al (2015) have recently found more genetic diversity in both CBSV and UCBSV, suggesting that there may be more than two viruses involved. Both virus groups belong to the genus Ipomovirus , and family Potyviridae (Mbewe et al , 2015); however, CBSV has a five times faster rate of evolution, and is more virulent compared with UCBSV (Alicai et al , 2016). Unlike CMBs, CBSVs are semi-persistent in B. tabaci (Maruthi et al , 2005).…”
Section: Plant Virus Transmission By B Tabacimentioning
confidence: 99%
“…However, in the lake zone of Tanzania, mean annual rainfall and the length of the growing season were the most important environmental factors. Some studies note generally when numbers of B. tabaci are likely to be low in cassava fields based on the time of the year when temperatures are low and the environment is unsuitable for B. tabaci (Mbewe et al , 2015). At a finer scale, we know that micro-climate variability within a field can influence the numbers of B. tabaci found on cassava plants.…”
Section: Abiotic Factorsmentioning
confidence: 99%
“…Recently there have been a number of surveys assessing the impact and extent of CMD and CBSD in sub-Saharan Africa. Much of the work has concentrated on assessing the per-field disease incidence and severity on a regional level (Alicai et al 2007; Chikoti et al 2013; Gondwe et al 2003; Hillocks et al 1999, 2002; Mbewe et al 2015; Mulenga et al 2018; Rwegasira and Rey 2012). Conducted surveys were based on field observations, without assessing growers’ knowledge in terms of (i) capacity to identify the viral diseases of cassava, (ii) practices related to sourcing and exchange of planting material, and (iii) control strategies.…”
Section: Introductionmentioning
confidence: 99%